Tinjauan Makna dan Bahasa Visual Iklan (Analisis Semiotika Iklan Gopay “Pevita Ditembak, JoTa Bertindak”) - Devont, Devont; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Gopay is a digital payment platform issued by Gojek Indonesia. Gopay often releases advertisements that have interesting ideas and concepts, such as the Gopay ad version of